2014
DOI: 10.1177/2167702613512793
|View full text |Cite
|
Sign up to set email alerts
|

A Behavior Genetic Analysis of Pleasant Events, Depressive Symptoms, and Their Covariation

Abstract: Although pleasant events figure prominently in behavioral models of depression, little is known regarding characteristics that may predispose people to engage in pleasant events and derive pleasure from these events. The present study was conducted to evaluate genetic and environmental influences on the experience of pleasant events, depressive symptoms, and their covariation in a sample of 148 twin pairs. A multivariate twin modeling approach was used to examine the genetic and environmental covariance of ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(88 reference statements)
1
4
0
Order By: Relevance
“…85 Therefore, the flow experience often serves as a protective factor against depression, positively contributing to alleviating depression. 50,51 Furthermore, this study also found that earning engagement mediates the relationship between TM and depression, with a mediation effect of 5.50%. In other words, the stronger an individual's TM, the higher their earning engagement, and the weaker their experience of depression.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…85 Therefore, the flow experience often serves as a protective factor against depression, positively contributing to alleviating depression. 50,51 Furthermore, this study also found that earning engagement mediates the relationship between TM and depression, with a mediation effect of 5.50%. In other words, the stronger an individual's TM, the higher their earning engagement, and the weaker their experience of depression.…”
Section: Discussionsupporting
confidence: 63%
“… 85 Therefore, the flow experience often serves as a protective factor against depression, positively contributing to alleviating depression. 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At Wave 2, approximately 10 years later, participants were recontacted and invited to again complete a telephone survey and a self-administered questionnaire. Note that several studies have reported findings from the MIDUS, including reports on depression (e.g., Sbarra, Emery, Beam, & Ocker, 2014; Whisman, Johnson, & Rhee, 2014) and LS (e.g., Röcke & Lachman, 2008; Staudinger et al, 2003). No studies to date, however, have focused on the issues addressed in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…In the rst session, patients were educated on the treatment rationale and executed an exercise in keeping up a mood diary. During the second session, patients added some potentially pleasant activities to their daily routine using the "pleasant activity list" (Lewinsohn & Amenson, 1978;MacPhillamy & Lewinsohn, 1982). In the following two sessions (3 and 4) patients developed and executed a pleasant activity plan.…”
Section: The Interventionmentioning
confidence: 99%